2018
DOI: 10.5433/1679-0359.2018v39n2p657
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cratylia argentea as an animal feed supplement in the control of gastrointestinal nematodes in sheep

Abstract: Gastrointestinal nematodes are considered one of the most important sanitary problems affecting ruminants globally; whether parasitizing alone or acting with other pathogens, they are responsible for severe economic losses related to animal husbandry. Endoparasites in small ruminants are usually controlled with anti-helminthic drugs. However, certain strains of endoparasites are resistant to such drugs. Supplementation of the diet with protein-rich foods is one strategy for reducing the negative impact of gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Las sustituciones que se proponen en las dietas con harinas, silos o forrajes verdes, provenientes del uso de las plantas proteicas, constituyen una opción económica, pues pueden sustituir materias primas para piensos sin afectaciones de los indicadores productivos y biológicos y de salud de los animales que las consumen (Silva, et al, 2018).…”
Section: Resultados Y Discusionunclassified
“…Las sustituciones que se proponen en las dietas con harinas, silos o forrajes verdes, provenientes del uso de las plantas proteicas, constituyen una opción económica, pues pueden sustituir materias primas para piensos sin afectaciones de los indicadores productivos y biológicos y de salud de los animales que las consumen (Silva, et al, 2018).…”
Section: Resultados Y Discusionunclassified
“…It is easily spread through seeds and is a leguminous plant, which performs biological nitrogen fixation (BNF) and contains high levels of crude protein (CP) (Matrangolo et al, 2018;Panadero et al, 2020). Due to its nutritional value, the species is promising for use in feeding different animal species, mainly ruminants (Mora et al, 2017;Silva et al, 2018). Sarria and Martens (2013) also found promising results evaluating the quality of C. argentea silage for swine feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found advantageous animal performance [8,9] and optimal nutritive value [10,11] with Cratylia. Braga et al [11] evaluated the ruminal degradability of Cratylia argentea, Flemingia macrophylla, and Stylosanthes guianensis harvested at 55 and 75 days Agronomy 2023, 13, 2525 2 of 12 and fed to growing sheep.…”
Section: Introductionmentioning
confidence: 99%